Prazer e gozo na toxicomania: como as drogas concernem ao social? - Costa, Márcio Clayton da Silva (2016)
The use and addiction on psychoactive substances have been a noticeable concern nowadays. Be it for its constant presence in the media or because it is a challenging matter for researchers and jurists, we consider this to be a relevant issue for our society. In such context, through theoretical research, based on the lacanian return to the freudian theories , we aim to analyze the phaenomenon of toxicomania through the perspective of the psychoanalysis. As we work with toxicomania through the psychoanalytic point-of-view, it implies that the unconsciousness is the basis of our considerations, so that our objective and interest is not the drug itself, but the effects on the subject which engages in such addiction. Taking into consideration that the subject cannot be reducted to individuality, we intend to analyze how the toxicomania refers also to the social structure. We aim to search for the theoretical foundations that justify the assumption that toxicomania is not a particular symptom, but one that relates to our current social structure. In order to meet these purpouses, it was necessary to articulate our major issue with concepts such as pleasure, repetition and jouissance.